2020
DOI: 10.1080/15252019.2020.1840459
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perceived Authenticity of Digital Enhancement of Model Advertising Images on Brand Attitudes, Social Media Engagement

Abstract: A flurry of advertising campaigns, legislative attempts to regulate digital modification (e.g., required disclaimers about digital modification required in France and other countries), and social movements like #MeToo have coincided with growing consumer desire for socially conscious advertising. The trend of creating socially conscious advertising is in line with consumer demand, but empirical evidence for how such advertising may affect consumer attitudes and behavior is lacking. This study investigates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The mechanism of perceived influencer authenticity highlights the distinction between the current research from previous research on ad model modification. Although Shoenberger and Johnson (2020) documented a positive effect of nonmodified ad models on ad effectiveness through authenticity, their mechanism is a feeling of image authenticity (measured by the extent to which consumers believe the image of the model is “realistic” or “truthful”), not person (ad model)'s authenticity. This distinction might be due to the different pathways ad model and influencers persuade.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of perceived influencer authenticity highlights the distinction between the current research from previous research on ad model modification. Although Shoenberger and Johnson (2020) documented a positive effect of nonmodified ad models on ad effectiveness through authenticity, their mechanism is a feeling of image authenticity (measured by the extent to which consumers believe the image of the model is “realistic” or “truthful”), not person (ad model)'s authenticity. This distinction might be due to the different pathways ad model and influencers persuade.…”
Section: Discussionmentioning
confidence: 99%
“…As reports show, luxury brands need to maintain a strong presence on social media channels as younger consumers live and breathe social media in a way that no other generation does. Furthermore, studies show that consumers' brand engagement on social media generates several benefits, such as stimulating purchasing intentions (Barton et al, 2016), increasing brand usage intention (Harmeling et al, 2017), and brand attitude (Shoenberger et al, 2020). This research focus on brand usage intention and brand attitude as outcome variables.…”
Section: Luxury Brands On Social Media and Brand Outcomesmentioning
confidence: 98%
“…Brand attitude and brand usage intention have been extensively examined by scholars as outcome variables in much of the advertising and marketing literature. Studies found that consumers' positive experiences of engaging with brands on social media generates positive brand attitude (Shoenberger et al, 2020;Song & Kim, 2020) and brand usage intention (Harrigan et al, 2018;Hollebeek et al, 2014;Sadyk & Islam, 2022).…”
Section: Luxury Brands On Social Media and Brand Outcomesmentioning
confidence: 99%
“…We propose that since offline (vs. online) shopping is construed as psychologically proximal (vs. distant), consumers are more likely to adopt a low construal level mindset and thus, prefer concretely framed naturalness. (Bae, 2020), naturalness (Wilks & Phillips, 2017), effectiveness (Davis et al, 2013), transparency (Rawlins, 2008), authenticity (Shoenberger et al, 2020), credibility (Kim & Cameron, 2011), engagement (Laczniak et al, 1999). Finally, respondents were asked to report their attitude toward the naturalness description being employed on the canned abalone.…”
Section: The Interactive Effect Of Shopping Channels and Message Fram...mentioning
confidence: 99%